The natural iron chelators' ferulic acid and caffeic acid rescue mice's brains from side effects of iron overload - Mahdi AAlikhani; Masoumeh Khalili; Masoumeh Khalili; Mehrdad Jahanshahi (Frontiers in Neurology, 2022)
Studies have shown that iron accumulation in the brain leads to neurogenic disorders. Novel iron chelating agents such as natural remedies are useful to decrease the side effects of iron in the brain. In addition, flavones and polyphenols are capable of chelating metals. In the current study, we evaluated the iron chelating capacity of ferulic acid and caffeic acid in the brain tissues of iron-overloaded mice. The mice received iron dextran intraperitoneally four times a week for 6 weeks. Next, blood samples were taken from the mice. In addition, brain tissues were excised for tissue staining as well as total iron and catalase (CAT) activity assessment. Ferulic acid and caffeic acid significantly decreased iron content in both brain and serum samples. Ferulic acid decreased iron by 50 and 51% more than the iron dextran-treated mice and by 43 and 2% more than desferal (DFO)-treated mice in serum and brain, respectively. In addition, caffeic acid reduced iron 57% more than the iron-treated group and 49 and 2% more than the desferal-treated group in the serum and brain, respectively. The catalase activity decreased with the increase in iron. By administering natural compounds, the catalase activity was increased equal to that of the control group. Thus, ferulic acid and caffeic acid might be possible natural iron chelators for brain iron overload therapy.